1993
DOI: 10.1099/00221287-139-7-1579
|View full text |Cite
|
Sign up to set email alerts
|

Production and regulation of potato-scab-inducing phytotoxins by Streptomyces scabies

Abstract: ~Phytotoxins with potato-scab-inducing activity were produced by the pathogenic Streptomyces scabies strain RB2 when grown on oatmeal agar medium or in oatmeal broth medium. Five compounds isolated from cell filtrates were identified as thaxtomin compounds 1-5, previously reported as produced by S. scabies grown on potato slices. The optimum temperature for phytotoxin production in oatmeal broth medium was 28 O C . Production of thaxtomin A, the major product, was repressed at least 130-fold when S. scabies RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 20 publications
4
40
1
4
Order By: Relevance
“…If we assume the monooxygenase catalyzed a single initial post-cyclization hydroxylation, then the most likely monooxygenase target would be the L-phenylalanyl ␣-carbon atom based on the logic of natural thaxtomin congener profiles found in extracts (1). This is because the only monohydroxylated thaxtomins that have been isolated from extracts and characterized are hydroxylated on the phenylalanyl ␣-carbon (thaxtomin B and thaxtomin 6) (19); thaxtomins carrying single hydroxyl groups on the phenylalanyl ring have not been identified in extracts.…”
Section: Discussionmentioning
confidence: 99%
“…If we assume the monooxygenase catalyzed a single initial post-cyclization hydroxylation, then the most likely monooxygenase target would be the L-phenylalanyl ␣-carbon atom based on the logic of natural thaxtomin congener profiles found in extracts (1). This is because the only monohydroxylated thaxtomins that have been isolated from extracts and characterized are hydroxylated on the phenylalanyl ␣-carbon (thaxtomin B and thaxtomin 6) (19); thaxtomins carrying single hydroxyl groups on the phenylalanyl ring have not been identified in extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Thaxtomins are unique 4-nitroindol-3-yl-containing 2,5-dioxopiperazines produced by at least three plant-pathogenic Streptomyces species (16,17,25). These toxins constitute a family of phytotoxic secondary metabolites that were originally purified from S. scabies-infected plant tissue (15,25) but are also produced in oatmeal-based media (1,26). Thaxtomin production is positively correlated with plant pathogenicity (17) and may be quantitatively related to virulence within S. scabies (26).…”
mentioning
confidence: 99%
“…Comparison of phytotoxin production in agar and liquid cultures with oatmeal, oat bran and potato peel media (Babcock et al 1993;Beauséjour et al 1999;Goyer et al 1998) showed that shake culture in potato peel broth provided high phytotoxin productivity and facilitated mass culture (Fig. S3), and this culture method was selected for further experiments.…”
Section: Isolation Of Phytotoxin Produced By S Turgidiscabies Strain 65mentioning
confidence: 99%
“…Phytotoxin production of S. turgidiscabies strains 65 and NBRC 16080 T The phytotoxicity of crude chloroform extracts of strain 65 and the type strain of S. turgidiscabies, NBRC 16080, cultured on oatmeal agar (Babcock et al 1993) was examined on rape seedlings. Extracts of both strains showed strong growth inhibitory activity at the dose corresponding to the amount of extract obtained from 10 mL of bacterial culture (Fig.…”
Section: Microarray Analysis Of Thaxtomin Biosynthetic Genes Of S Tumentioning
confidence: 99%